Capital Accessibility and Financial Inclusion in Elevating MSMEs Financial Performance - Nur Fitri Dewi (CV. ITTC INDONESIA, 2025)
As MSMEs in Indonesia continue to evolve, their development faces various challenges, particularly regarding the improvement and long-term maintenance of their financial performance. This problem is caused by the many capital challenges faced and the lack of financial inclusion in MSMEs. This study aimed to determine the impact of capital accessibility and financial inclusion on the financial performance of MSMEs in Sukarami District, Palembang City. The study's population consisted of MSMEs in Sukarami District, Palembang City, with data collected through a questionnaire distributed to 100 MSME respondents in the area. The gathered data were analyzed using SPSS 27.00, employing Multiple Linear Regression Analysis, t-tests, and F-tests. The results revealed that capital accessibility and financial inclusion partially have a significant positive effect on the financial performance of MSMEs in Sukarami District. Furthermore, capital accessibility and financial inclusion simultaneously also have a positive effect on the financial performance of MSMEs in Sukarami District. These findings provide valuable insights for MSMEs, offering input and considerations to enhance their financial performance, particularly in Sukarami, Palembang.